2002
DOI: 10.1159/000066003
|View full text |Cite
|
Sign up to set email alerts
|

CD156 Transgenic Mice

Abstract: CD156 (ADAM8) is part of the ADAM family of proteins with the catalytic site consensus sequence of metalloprotease and disintegrins. To examine the role of CD156 in vivo, we generated mutant CD156 (eCD156) transgenic mice expressing the ectodomain of CD156 under the control of the α1-antitrypsin (AT) promoter. One of the transgenic mice designated ATMS2-TG18 expressed a 1.84 kb mRNA which was predicted to be a truncated CD156. The expression of the transgenic CD156 mRNA in ATMS2-TG18 mice was abundant in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Regarding the other zinc-binding proteases downregulated in the GCF of AD patients, disintegrin and metalloproteinase ADAM8 and 9 act as inducing inflammation or anti-inflammation responses, under specific conditions. ADAM8 and 9 have not been previously studied in AD [22,23]. In line with our results, a previous study reported a higher ADAM9 expression in normal mucosa compared to the inflamed gastric mucosa, suggesting that the decreased ADAM9 may predispose to chronic mucosal inflammation [23].…”
Section: Ad Is a Chronic Inflammatory Dermatosis Characterized By An Abnormal Skin-barrier Functionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding the other zinc-binding proteases downregulated in the GCF of AD patients, disintegrin and metalloproteinase ADAM8 and 9 act as inducing inflammation or anti-inflammation responses, under specific conditions. ADAM8 and 9 have not been previously studied in AD [22,23]. In line with our results, a previous study reported a higher ADAM9 expression in normal mucosa compared to the inflamed gastric mucosa, suggesting that the decreased ADAM9 may predispose to chronic mucosal inflammation [23].…”
Section: Ad Is a Chronic Inflammatory Dermatosis Characterized By An Abnormal Skin-barrier Functionsupporting
confidence: 87%
“…This was also true for the expression of L-selectin in PMN from peripheral blood samples. These results suggest that ADAM8 might activate endothelial cells and lead to the upregulation of E-selectin, thus regulating leukocyte infiltration directly or indirectly [22]. Therefore, it could be expected that ADAM8 and 9 would be detectable in the GCF samples of healthy controls, regulating leukocyte infiltration as a defensive mechanism of periodontal tissues [22].…”
Section: Ad Is a Chronic Inflammatory Dermatosis Characterized By An Abnormal Skin-barrier Functionmentioning
confidence: 95%
“…Reduction of CD44 by HAS1 expression may negatively regulate normal in vivo migratory properties of HSCs ( 23 ). In contrast with hESC-derived cells, somatic cells expressed substantially higher levels of CXCR4, CD44, and l-selectin, which are involved in appropriate homing and engraftment behavior of candidate human HSCs ( 24 , 25 ), as well as matrix metalloproteinases, ADAM8 ( 26 ) and ADAM17 ( 27 ) that are involved in establishing HSC residence within the BM niche.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that Adam9 was not essential for PMNs (or macrophages) to accumulate in the lungs during LPS- or bleomycin-mediated ALI in mice suggesting that neither the MP nor the disintegrin domain of PMN or monocytes/macrophage-derived ADAM9 regulate inflammatory cell recruitment into the lung. In contrast, the MP domains of PMN-derived Adam-8 and -17 regulate inflammatory responses in tissues by shedding L-selectin, TNF-α, and TNF receptors from PMN surfaces (6668). During LPS- and bleomycin-mediated ALI, Adam9 promoted lung injury and reduced lung compliance without altering lung inflammatory cell counts in mice.…”
Section: Discussionmentioning
confidence: 99%